Group analysis a modern synthesis - Karterud, Sigmund (The new international library of group analysis, 2024)
Group Analysis outlines how clinical group analysis can re-establish itself as a leading paradigm for group psychotherapy. Sigmund Karterud explains how the focus of group analysis and its applications can be expanded by stronger emphasis on the philosophy and psychology of the self. The book is divided into four parts, with part one reconsidering the historical roots of group analysis through its founder S. H. Foulkes and part two demonstrating how the fields of evolution, primary emotions, attachment, mentalizing, personality theory and personality disorders can be integrated with group analysis. Part three develops a philosophy of the self that includes a group self which accounts for the we-ness of groups, and part four illustrates how these concepts can inform the practice of group analysis through a series of clinical vignettes addressing the major challenges which face the clinician. Group Analysis: A Modern Synthesis will be essential reading for all group psychotherapists in practice and in training. It will also appeal to students of group analytic psychotherapy"-- Provided by publisher.